Do patients and other stakeholders value health service quality equally? A prospect theory based choice experiment in cataract care - Stolk-Vos, Aline C.; Attema, Arthur E.; Manzulli, Michele; van de Klundert, Joris J. (Social science & medicine (1982), 2022)
This study aims to compare the valuation of health service quality by patients and other stakeholders through a case study in cataract care. The valuation of health service quality by Dutch patients, ophthalmologists and healthcare purchasers involved in cataract care are elicited by a prospect theory-based measurement task. Respondents stated preferences for probabilities and scores for the clinical indicator Complication (posterior capsular rupture with vitreous loss) and the patient-reported experience measure Information Provisioning (the ophthalmologist provides sufficient information about risks of cataract surgery to the patient). Our subject pool (n = 256) consisted of 90 ophthalmologists, 125 cataract patients, and 41 healthcare purchasers employed by health insurance companies. Following prospect theory, respondents were loss averse, and risk averse for gains. However, utilities differed from prospect theory, especially the concave utility for losses. Patients were significantly more loss averse than the other respondents, more subject to a pessimistic view on losses, and had significantly more concave utility for losses, especially for the clinical quality indicator Complications. For each of the stakeholders, the results differed significantly between the two essentially different quality indicators. The heterogeneous valuations of patients and other stakeholders invalidate commonly applied cataract care quality assessment frameworks. Incorporating loss aversion, pessimism and concave utility for losses can remedy existing shortcomings. The valuation differences between patients and other stakeholders emphasize the need for communication and shared decision making in patient-centered treatment, purchasing and policy. •Patients' valuation of quality indicators differs from other stakeholders.•Patients are more averse to loss and risk of healthcare quality than others.•Rankings misrepresent stakeholders valuations.•To be representative of stakeholders, frameworks need to adopt nonlinear valuations.